2020
DOI: 10.1016/j.breast.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of BET inhibitors in breast cancer

Abstract: Bromodomain and extraterminal domain (BET) proteins are epigenetic molecules that regulate the expression of multiple genes involved in carcinogenesis. Breast cancer is an heterogenous disease emerging from aberrant gene expression and epigenetic alteration patterns. Amplification or overexpression of BET proteins has been identified in breast tumors highlighting their clinical significance. Development of BET inhibitors that disrupt BET protein binding to acetylated lysine residues of chromatin and suppress t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 111 publications
(219 reference statements)
0
27
0
Order By: Relevance
“… 53 In clinical trials, it has been found that thrombocytopenia is the most important toxicity of BET inhibitors; gastrointestinal diseases, anemia, and fatigue are the most common adverse events related to BET inhibitor treatment. 54 The combination of JQ1 and other drugs can not only enhance the efficacy but also effectively inhibit the side effects of drug treatment. 55 , 56 Our research shows that BRD4 can regulate the growth of melanoma cells through the mitochondrial pathway and that BRD4 inhibition impairs the mitochondrial function of B16 cells, leading to energy metabolism dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 In clinical trials, it has been found that thrombocytopenia is the most important toxicity of BET inhibitors; gastrointestinal diseases, anemia, and fatigue are the most common adverse events related to BET inhibitor treatment. 54 The combination of JQ1 and other drugs can not only enhance the efficacy but also effectively inhibit the side effects of drug treatment. 55 , 56 Our research shows that BRD4 can regulate the growth of melanoma cells through the mitochondrial pathway and that BRD4 inhibition impairs the mitochondrial function of B16 cells, leading to energy metabolism dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although JQ1 has become a research hotspot in the last five years due to its highly specific recognition site, good cell permeability, and low toxic and side effects, its short half‐life may lead to increased toxicity and side effects of the drug, which limits its clinical application 53 . In clinical trials, it has been found that thrombocytopenia is the most important toxicity of BET inhibitors; gastrointestinal diseases, anemia, and fatigue are the most common adverse events related to BET inhibitor treatment 54 . The combination of JQ1 and other drugs can not only enhance the efficacy but also effectively inhibit the side effects of drug treatment 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomain proteins can further be subdivided into two families, the BET and non-BET families, on the basis of their structural parameters [ 46 ]. BET proteins are directly associated with transcription and maintaining the effective progression of the cellular cycle [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This led to the prediction that using bromodomain inhibitors in addition to the standard therapy may reduce the development of resistance in some cancers [ 313 ]. Combinations of epigenetic therapeutics have also proven successful in the treatment of acute myeloid leukemia [ 314 ], multiple myeloma [ 315 ], pancreatic cancer [ 316 ], ovarian cancer [ 317 ], and in breast cancer [ 318 ]. One mechanism for this synergy has been outlined through the dual inhibition of BET bromodomains in combination with poly[adenosine diphosphate (ADP)-ribose] polymerase inhibitors (PARPi).…”
Section: Emerging Strategies To Target Bromodomain Proteinsmentioning
confidence: 99%